PENDEKATAN PREVENTIF DALAM MENCEGAH PERMASALAHAN DAN MENUMBUHKAN KARAKTER SISWA KELAS XII MIPA SMA NEGERI 1 SELEMADEG - I Ketut Sudiatmika (Widyadari, 2024)
Preventive action in classroom management is the prevention of deviant behavior. Preventive efforts are social control in the form of preventing disturbances. However, there are still some students who lack religious character and discipline, such as some students who still violate school rules, there are students who do not participate in activities who are less polite in speaking, lack respect for their teachers, and there are students who experience obstacles in character building. The aim of this research is to find out how to take a preventive approach in preventing problems and developing the character of class XII MIPA students at SMA Negeri 1 Selemadeg. This research is descriptive qualitative field research. Data collection techniques were obtained through observation, interviews and documentation. The collected data was analyzed by data reduction, data description, interpretation, strengthening theory and then drawing conclusions. The results of research carried out at SMA Negeri 1 Selemadeg Tabanan in 2024 show that there are preventive efforts by guidance and counseling teachers in shaping student character, so that guidance and counseling teachers have carried out several efforts to shape student character, namely religious character and disciplinary character. This character formation is also instilled in students through the regulations implemented at school. Preventive social control is prevention before there is a deviation from the norms and values ​​of society given to students